2008
DOI: 10.1002/cbdv.200890096
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Umami (Enhancing) Molecules

Abstract: As health has become one of the main drivers in nutrition, the scientific interest in taste receptors and taste molecules has increased considerably. Academia as well as flavor and food companies are searching for molecules that make food more healthy but not less appetizing. In the savory area, salt and umami taste are being investigated. This review deals with the progress made in umami tasting molecules. Umami taste has been known as a separate taste for a long time in Asian countries and has been generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
2
50
0
6
Order By: Relevance
“…N- (heptan-4-yl) benzo [d] [1,3]dioxole-5-carboxamide (S807; Senomyx; Table 1) is indeed a molecule that stimulates recombinant umami receptors directly by interacting with the 7TM domain of T1R1 (Zhang et al, 2008a). As a result of the efforts in the food industry to identify novel taste enhancers, many other umami-tasting molecules obtained and derived from different sources and leads and with different binding sites and mechanisms have been described previously (Winkel et al, 2008).…”
Section: Allosteric Modulation Of Family C Gpcrsmentioning
confidence: 99%
“…N- (heptan-4-yl) benzo [d] [1,3]dioxole-5-carboxamide (S807; Senomyx; Table 1) is indeed a molecule that stimulates recombinant umami receptors directly by interacting with the 7TM domain of T1R1 (Zhang et al, 2008a). As a result of the efforts in the food industry to identify novel taste enhancers, many other umami-tasting molecules obtained and derived from different sources and leads and with different binding sites and mechanisms have been described previously (Winkel et al, 2008).…”
Section: Allosteric Modulation Of Family C Gpcrsmentioning
confidence: 99%
“…Recently, it was found that hydroxy-a-sanshool excites the D-hair fibers, a distinct subset of ultrasensitive lighttouch receptors in the skin and targets novel populations of Ab and C fiber nerve afferents (Lennertz et al, 2010). Above, NAAs are found to have remarkably strong umami tasting properties (Winkel, et al, 2008). Umami-taste can be described as salty and brothy and has been recognized as the fifth basic taste sensation next to sweet, salt, bitter and sour.…”
Section: Tingling and Related Organoleptic Effectsmentioning
confidence: 99%
“…Umami-taste can be described as salty and brothy and has been recognized as the fifth basic taste sensation next to sweet, salt, bitter and sour. The umami taste is associated with a G-protein-couple receptor, but the question which receptor protein is responsible, and if there are more proteins important, remains unclear at this moment (Winkel, et al, 2008). Several patents claim the taste and flavor enhancing effect of food, drinks and drugs by NAAs, which have sweet, salt or umami taste and flavor enhancement quality.…”
Section: Tingling and Related Organoleptic Effectsmentioning
confidence: 99%
“…Eine Analyse der Peptide in Proteinhydrolysaten aus Gemüse lieferte Pyroglutamyl-Peptide wie pGlu-Pro-Ser, pGlu-Pro, pGlu-Pro-Glu und pGlu-Pro-Gln als wichtige Moleküle mit umamiartigem Geschmack in diesen flüssigen Würzungen. [67,68] Zudem führte die enzymatische Hydrolyse von Fischproteinen zu herzhaften Produkten, die reich an sauren Peptiden wie AspGlu-Ser, Glu-Asp-Glu, Thr-Glu und Ser-Glu-Glu waren. [69] Solche sauren Di-und Tripeptide zeigten selbst nur eine schwache Umamiaktivität, die aber in Gegenwart von IMP deutlich verstärkt wurde.…”
Section: Mabinlinunclassified
“…[79] Neben der Identifizierung solcher natürlichen Umamigeschmacksverstärker in rohen und verarbeiteten Nahrungsmitteln über den Sensomik-Ansatz konzentrieren sich andere Forschungsansätze auf die thermische Reaktion bekannter, isolierter Nahrungsmittelbestandteile unter küchenüblichen Modellbedingungen, das Screening der zur Geschmacksverstärkung gebildeten Reaktionsprodukte durch sensorische Prüfungen mithilfe menschlicher Testpersonen und die nachfolgende Verifizierung des natürlichen Vorkommens dieser Verbindungen in Nahrungsmitteln durch HPLC-MS/ MS. Zum Beispiel wurde N-Gluconylethanolaminphosphat (43) durch Reaktion von 2-Aminoethyldihydrogenphosphat und d-Gluconolacton erhalten und eine umamiverstärkende Wirkung festgestellt. [68] N-Gluconylethanolamin, dem ein natürlicher zuckerartiger Geschmackscharakter zugeschrieben wurde, wurde in "Beerenauslese"-Weinen nachgewiesen. [80] Erhitzung von Guanosin-5'-monophosphat (38) in Gegenwart von Essigsäure oder Milchsäure führte zu N-Acetyl-(44) bzw.…”
Section: Mabinlinunclassified